Bilateralism and regionalism : re-establishing the primacy of multilateralism : a Latin American and Caribbean perspective - Kuwayama, Mikio (CEPAL SantiagoCL, 2005)
Presents regional perspectives on the multilateral trading system and the Doha development agenda. Looks at existing and emerging free trade agreements in the region as well as the Free Trade Area of the Americas and other initiatives. Focuses on subregional integration and bilateral agreements.